A note on 1-semi-greedy bases in p-Banach spaces with 0 < p ≤ 1 - Berná Pablo M.; García Andrea; González David (Demonstratio Mathematica)
The purpose of this article is to discuss about the so-called semi-greedy bases in pp-Banach spaces. Specifically, we will review existing results that characterize these bases in terms of almost-greedy bases, and, also, we analyze quantitatively the behavior of certain constants. As new results, by avoiding the use of certain classical results in pp-convexity, we aim to quantitatively improve specific bounds for bi-monotone 1-semi-greedy bases.